GamReg Sweden—Protocol for a systematic cohort data collection for improved clinical knowledge in specialized gambling disorder treatment - Håkansson, Anders; Åkesson, Gunny (Frontiers in Psychiatry, 2022)
Background Gambling disorder is the first non-substance-related addiction which is recognized as a diagnostic entity and assessed in treatment settings. However, in many clinical settings, assessment and structured treatment for this condition is severely under-developed, and treatment seeking in many settings is low. This is a protocol paper describing the rationale and structure of a recently established quality register, allowing for structured monitoring of treatment seeking, treatment needs and treatment provision in Swedish health care settings, for gambling disorder and associated conditions. Methods Since 2019, a Swedish quality register is in use for the systematic data collection from patients receiving treatment in specialized health care. The register is held by Region Skåne, and approved for national use. Swedish quality registers allow for the clinical monitoring of treatment uptake and needs, for quality improvement purposes, and collect systematic cohort data for these purposes. In addition, these quality registers potentially allow for future research projects, after separate ethics applications, allowing for clinical follow-up studies based on non-identified quality register data. Clinical challenges and research knowledge gaps are addressed in the present register, including mental health comorbidity, history of suicidal behavior, comorbid alcohol, drugs and gaming behaviors, and fundamental psycho-social variables such as violence victimization, concerned significant others including children’s situation in families of problem gamblers, and main income and involvements with social services and enforcement agency. In addition, patient flows, including rates of referral from primary care and other treatment settings, can be followed. The overall quality register project is registered at clinicaltrials.gov (NCT05276193). Discussion The present protocol paper will allow for systematic reporting and future projects addressing knowledge gaps in clinical treatment for gambling disorder, and highlight the importance for evidence-based treatment in a behavioral addiction. Importantly, the current data will contribute to a better understanding of which patient groups may be less likely to seek or to be referred to treatment, and thereby may shape future initiatives to increase screening and referral in targeted, vulnerable groups.